2014
DOI: 10.1021/la503542b
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Foamability of Sodium Dodecyl Sulfate Surfactant Mixed with Superspreader Trisiloxane-(poly)ethoxylate

Abstract: Gravitational drainage from thin vertical surfactant solution films and gravitational drainage in a settler column are used to study the behavior of foams based on two-surfactant mixtures. Namely, solutions of the anionic sodium dodecyl sulfate (SDS) and nonionic superspreader SILWET L-77, and their mixtures at different mixing ratios, are studied. It is shown, for the first time, that solutions having a longer lifetime in the vertical film drainage process also possess a higher foamability. An additional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…The addition of PTS to the SDS solutions gives rise to improved initial foam height for the binary mixtures, indicative of the promotion in the foaming ability of SDS solutions with increasing PTS concentration. Similar results have been reported by Sett et al [29]. The initial foam height is found to gradually rise with the increase in SDS concentration at a given PTS content.…”
Section: Foam Propertiessupporting
confidence: 91%
See 2 more Smart Citations
“…The addition of PTS to the SDS solutions gives rise to improved initial foam height for the binary mixtures, indicative of the promotion in the foaming ability of SDS solutions with increasing PTS concentration. Similar results have been reported by Sett et al [29]. The initial foam height is found to gradually rise with the increase in SDS concentration at a given PTS content.…”
Section: Foam Propertiessupporting
confidence: 91%
“…This means that the lowered surface tension, in a way, promoted foam stability. Besides, Sett's [29] studies showed that the plane films formed from mixture solutions exhibited a higher disjoining pressure as compared to the corresponding films of SDS-alone or SILWET L-77 (one of silicone surfactants)-alone solutions. Therefore, maybe the higher disjoining pressure occurred to mixed systems of hydrocarbon surfactant/PTS and stabilized the foams generated by mixture solutions.…”
Section: Foam Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned earlier, N70K-T was a blend of nonionic surfactant and alcohol and both individual substances were added at given concentrations. Sett et al [23] reported that the foamability of nonionic/anionic surfactant mixture solution could be greater than the foamability of either of them separately, and they also pointed out that the primary cause of the foamability enhancement might be the higher disjoining pressure which generated thinner but more stable lamella. Thus/Therefore, in this experiment, larger volumes of foam /were created from the mixture solution below an additive concentration of 0.4 wt.…”
Section: Accumulative Oil Recoverymentioning
confidence: 99%
“…Aqueous foam is considered as a colloidal system consisting of dispersed gas phase and a continuous liquid phase, stabilized in most cases by surfactant molecules adsorbed on the gas–liquid, which has wide applications not only in our daily life, for example, cosmetics and detergents, but also in many industrial regions such as mineral floatation, electromagnetic interference shielding, and enhanced oil recovery (EOR), etc. In most of the practical occasions, good foam stability is required . Numerous studies on the factors affecting the foam stability have been done, among them, the types and concentration of the surfactants and the additives and the temperature were all recognized to be the core ones that could play an important role on changing foam stability through diverse mechanisms. …”
Section: Introductionmentioning
confidence: 99%